E-Government Adoption By Public Sector Employees In Dhaka. - MIAH, MD SHUHEL; SENTOSA, ILHAM (The journal of contemporary issues in business and government, 2021)
E-government essentially asserts the use of ICT, especially, use of internet to achieve better governments. Governments around the world, both developed and developing nations are trying to implement e-services. E-government is believed to enhance efficiency, transparency and facilitate the better work flow among public sector employees. However, the intentions of the public sector employees are influenced by several factors to adopt e-government. This study aims to identify the factors influencing the intention of the public sectors employees in Dhaka. TAM, DOI, UTAUT and UMEGA theories have been used to examine the factors. The factors which are derived from the literature are Perceived Usefulness, Perceived Ease of Use, Perceived Compatibility, Attitude, Social Influence and Performance Expectancy. Smart PLS 3.0 has been used as statistical tool to analyze the data and tests the conceptual model by using structural equation modeling. The finding of the study reveals the significant factors influencing the intention of the public sector employees in Dhaka. Research implications of this study are discussed.